Penggunaan Teknik Spuit dalam Meningkatkan Kemampuan Menggambar Pada Anak Tunarungu Kelas VIII di SLB Dorkas Kakas - Aldjon Nixon Dapa; Femmy Debora Siwi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the improvement in drawing ability using the syringe technique in class VIII students at SLB Dorkas Kakas. This research is experimental research with a Single Subject Research (SSR) experimental approach with an A1-B-A2 design. The research subjects were class III mildly deaf students aged 14 years, namely TR subjects. Data collection uses performance tests, observation and documentation during the implementation of baseline-1, intervention and baseline-2. The data obtained was analyzed through descriptive statistics and displayed in graphical form. The components analyzed are analysis within conditions and analysis between conditions. Data collection is through measuring drawing ability using performance tests. Based on the research results, during the implementation of the Spuit technique and during the intervention session progress was shown in the form of activeness, namely students actively responded during the lesson and were enthusiastic in participating in the learning process and were able to concentrate well if there were no internal or external distractions. In addition, there is an increase in the subject's ability to draw. The mean level of TR subjects increased from 7.18 at baseline-1 (A-1) to 11.1 at intervention (B) and 12.23 at baseline-2 (A-2). The results of this research indicate that through implementing the Spuit technique the drawing ability of class VIII mildly deaf students can be improved. Thus, it can be concluded that the Spuit Technique can improve drawing abilities.